Fabrication of a Screen-Printed E-Textile Interdigitated Capacitive Sensor for Measuring Stratum Corneum Hydration - Alexandar R. Todorov; Russel Torah; Michael Ardern-Jones; Stephen Beeby (Engineering Proceedings)
This work describes the fabrication and testing of an interdigitated capacitive sensor, embedded in a wearable e-textile for non-invasive in vivo monitoring. The sensor is sensitive to moisture changes within the stratum corneum layer (SC) of the skin. Testing is conducted by measuring the hydration state of the skin before and after the application of moisturizing agents to the SC, and the readings are mapped to a commercial gold standard measurement of skin hydration using the Corneometer®. The results confirm that the interdigitated sensor can accurately detect the change in the hydration state of the SC with a sensitivity of 1.29 pF per arbitrary units of hydration.